Uji kadar total polifenol buah asam kandis (Garcinia xanthochymus Hook.f.ex T.Anderson) dengan metode spektrofotometri UV-VIS dan LCMS - Winata, Hanafis Sastra; Faisal, Hendri; Andry, Muhammad; Naziyah, Syifa; Nasution, Muhammad Amin (Journal of Pharmaceutical and Sciences, 2023)
Background: Kandis tamarind has various activities, such as antioxidant, cytotoxic, anti-inflammatory, and antimicrobial. This study aimed to determine the total polyphenol content of kandis acid fruit and the types of phenolic compounds contained in kandis acid fruit. This type of research was experimental, using 70% ethanol solvent. The research method used was a polyphenol qualitative test, UV-Vis spectrophotometry, and LC-MS. The results of qualitative measurements showed that the samples contained polyphenolic compounds. The results of the polyphenol test on the kandis acid fruit sample on 1% FeCl3 reagent and diazo reagent got positive results, while the Millon reagent got negative results. The study's results show that the determination of the levels of polyphenol content in kandis acid fruit extract was measured using UV-VIS spectrophotometry by adhering to the working principle of Folin-Ciocalteau. The proof of polyphenol content used the Folin-Ciocalteau reagent because this reagent can react with a group of polyphenolic compounds to form a concentrated solution whose absorbance can be measured. The higher the sample concentration, the higher the absorbance value. The results of determining the polyphenol content of the kandis acid fruit extract using uv-vis spectrophotometry had a polyphenol compound component of 61.1015 mg GAE/g sample. The results of the LC-MS analysis for the highest phenolic compound, namely the type of vanillic acid, amounted to 14.21%.